Molecular and morphological analyses reveal pseudocryptic diversity in Micromelo undatus (Bruguière, 1792) (Gastropoda: Heterobranchia: Aplustridae). Issue 7 (3rd October 2021) - Feliciano, Kendall; Malaquias, Manuel António E.; Stout, Carla; Brenzinger, Bastian; Gosliner, Terrence M.; Valdés, Ángel
Abstract : The genus Micromelo (family Aplustridae) occurs in almost all tropical and subtropical waters across the globe, with the exception of the Eastern Pacific. Most authors consider Micromelo undatus (Bruguière, 1792) as the only valid species in this genus. This study examines populations of specimens identified as M. undatus across its geographic range, using morphological and genetic data from two mitochondrial genes (16S and CO1) and one nuclear gene (Histone H3). The results reveal that M. undatus is a complex of four species with consistent genetic and anatomical differences. A literature review and evaluation of type material indicates that available names exist for three of the four species. Micromelo guamensis, M. undatus and M. scriptus are resurrected for species found in the Western Pacific, the Atlantic Ocean, and widespread in the Indo-Pacific, respectively. A new name is introduced for another species found in the Western Pacific, namely Micromelo barbarae sp. nov. and a neotype is designated for the type species of the genus M. undatus . http://zoobank.org/urn:lsid:zoobank.org:act:02091D97-0AE1-4AE4-9910-726C4F0ABE2F